Implementasi Strategi Pemasaran Digital untuk Pengembangan UMKM di Pesantren Khalifa: Pendekatan Halal dan Digitalisasi Pasar - Mukhlishah; Kurniasih, Imas; Muhtadin; Mulyani, Yani (Bayani, 2024)
Community service program carried out through digital marketing training for MSMEs located at the Khalifa Islamic Boarding School. This program aims to improve the skills of MSMEs in using digital technology as a tool to expand their market coverage. With an approach that integrates halal principles, this training not only teaches digital marketing, but also ensures that the products being promoted meet the criteria in accordance with religious teachings. At the end of the activity, it is hoped that a strong network will be created between local MSMEs and the wider market, as well as increasing the competitiveness of MSMEs through the use of digital marketing.